Growth and survival of catfish (Clarias gariepinus) with addition of papain enzymes in feed at Karang Dapo Village, Pagaralam, South Sumatera - Nuraisyah, Alni; Mukti, Retno Cahya (Universitas Malikussaleh, 2022)
Catfish (Clarias gariepinus) is a freshwater fish that is widely cultivated in Indonesia. Production cost of fish farming activities spend 60-70% on the use of feed. Therefore, feeding must be effective and efficient so that catfish can make good use of it for its growth. The addition of an exogenous enzyme in the form of papain enzyme can increase the efficiency of feed utilization. The purpose of this study was to determine the effect of the addition of the enzyme papain in feed on the growth and survival of sangkuriang catfish (Clarias gariepinus). The treatments consisted of P0: control (without the addition of the papain enzyme) and P1: treatment with the addition of the papain enzyme with a dose of 1.5 mg kg-1 of feed. The parameters observed were absolute weight growth, absolute length growth, feed efficiency, survival, and water quality. The results showed that the addition of the enzyme papain to the feed produced the highest of absolute weight growth 19.97 g, absolute length growth 7.74 cm, feed efficiency 90.25%, survival rate 90%, and water quality such as temperature from 24.3 - 28.3 0C and pH 7.2 - 7.4. Keywords: catfish, feed, papain enzyme